Efficiency of invasive revascularization for acute coronary syndrome with ST elevation: first results of Regional Vascular Center of the Buryat Republic - L. B. Sodnomova; N. O. Bulutova (Acta Biomedica Scientifica, 2017)
The primary and main method of treating ACS with ST elevation is timely restoration of coronary vessel patency. Material and methods. 273 medical records of patients admitted with provisional diagnosis of ACS with ST elevation were studied. Statistical data were processed in Microsoft Excel and Statistica 10 (StatSoft Inc., USA). Results. One third of patients with ACS with ST elevation were admitted at «the golden hour» since symptoms onset. 234 (86 %) patients underwent coronary angiography. Primary percutaneous intervention (PCI), coronary stenting were performed for 117 patients, thrombolysis - for 23 and thrombolysis with subsequent PCI was carried out in 34 cases. Assessment of RCI efficiency, invasive revascularization in terms of IM frequency and mortality showed the following: the incidence of myocardial infarction in the group with PCI and without PCI was the same - 94 % against 98 % respectively; however the mortality in patients with STEMI was lower in the group with performed invasive revascularization - 4 % against 12 % (р = 0.04). Decrease is observed in both total mortality and mortality in the first 24 hours for STEMI patients - 3 % in the PCI group, compared to 9 % in the other group (р = 0.04). The suvival rate for STEMI patients was better for first time PCI - mortality 2.7 % against 12 % in the group without revascularization (р = 0.01).